Levels of plasmacytoid dendritic cells and type-2 myeloid dendritic cells are reduced in peripheral blood of patients with primary Sjögren's syndrome. Issue 6 (12th November 2009) - Vogelsang, Petra; Brun, Johan G; Øijordsbakken, Gunnvor; Skarstein, Kathrine; Jonsson, Roland; Appel, Silke
Abstract : Objective: Sjögren's syndrome (SS) is a lymphoproliferative autoimmune disease, characterised by dryness of the mouth and eyes. Dendritic cells (DC) are potent antigen-presenting cells crucial for initiating and maintaining primary immune responses. This study quantified interferon-producing plasmacytoid DC (pDC) and two myeloid DC subsets (mDC1 and mDC2) in peripheral blood (PB) from primary SS (pSS) patients and healthy controls. Methods: Blood samples from 31 pSS patients and 28 gender and age-matched healthy controls were analysed by flow cytometry using the Miltenyi Blood DC enumeration kit. The presence of pDC in salivary glands (SG) from pSS patients was analysed by immunohistochemistry. Results: Patients with pSS had significantly less pDC and mDC2 in PB compared with healthy controls. Moreover, pDC are present in SG from patients with pSS. Conclusion: Patients with pSS have alterations among DC populations in PB, and pDC are present in the SG, suggesting a potential role of these cells in SS.